Sub-100 fs formation of dark excitons in monolayer WS2 - Kolesnichenko, Pavel V.; Wittenbecher, Lukas; Zhang, Qianhui; Teh, Run Yan; Babu, Chandni; Fuhrer, Michael S.; Mikkelsen, Anders; Zigmantas, Donatas (Nano letters, 2024)
Two-dimensional semiconducting transition metal dichalcogenides are promising materials for optoelectronic applications due to their strongly bound excitons. While bright excitons have been thoroughly scrutinized, dark excitons have been much less investigated, as they are not directly observable with far-field spectroscopy. However, with their nonzero momenta, dark excitons are significant for applications requiring long-range transport or coupling to external fields. We access such dark excitons in WS2 monolayer using transient photoemission electron microscopy with subdiffraction limited spatial resolution (75 nm) and exceptionally high temporal resolution (13 fs). Image time series of the monolayer are recorded at several different fluences. We directly observe the ultrafast formation of dark K-Λ excitons occurring within 14-50 fs and follow their subsequent picosecond decay. We distinguish exciton dynamics between the monolayer’s interior and edges and conclude that the picosecond-scale evolution of dark excitations is defect-mediated while intervalley scattering is not affected by the defects.
Online veröffentlicht: 8. November 2024
Gesehen am 25.06.2025